Post-Traumatic Duodenal Stenosis Following a Duodenal Hematoma : Case Report and Review of the Literature (Global Journal of Medical Research, 2020)
Post-traumatic duodenal hematoma is a rare condition after an abdominal trauma the diagnostic is difficult because of the retro-pancreatic situation of the duodenum 70 of duodenal hematomas occur after closed abdominal trauma The first case of duodenal hematoma was published in 1838 by McLaughlan The clinical signs are non-specific and vary according to the site of the hematoma in the four portions of the duodenum The diagnosisis based on imaging in particular abdominal CT scan the management has completely changed towards a more conservative strategy by reserving surgery for persistent obstruction and expansion of the hematoma We report a case of a patient victim of a road traffic accident resulting in a blunt abdominal trauma manifested bysigns of high occlusion whose abdominal CT scan showed the presence of a duodenal hematoma compressing the 3rd portion of the duodenum responsible for gastric and esophageal distension treated by a conservative method
Keywords: duodenal hematoma; abdominal trauma; surgery